In vivo biomechanical behavior of the trapeziometacarpal joint in healthy and osteoarthritic subjects. (November 2017) - D'Agostino, Priscilla; Dourthe, Benjamin; Kerkhof, Faes; Harry Van Lenthe, G.; Stockmans, Filip; Vereecke, Evie E.
Abstract: Background: The contact biomechanics of the trapeziometacarpal joint have been investigated in several studies. However, these led to conflicting results and were mostly performed in vitro. The purpose of this study was to provide further insight on the contact biomechanics of the trapeziometacarpal joint by in vivo assessment of healthy and osteoarthritic subjects. Methods: The hands of 16 healthy women and 6 women with trapeziometacarpal osteoarthritis were scanned in positions of maximal thumb extension, flexion, abduction and adduction during three isometric tasks (lateral key pinch, power grasp and jar twist) and in thumb rest posture (relaxed neutral). Three-dimensional surface models of the trapezium and first metacarpal were created for each thumb configuration. The articular surface of each bone was measured in the neutral posture. A computed tomography-based proximity mapping algorithm was developed to calculate the distance between opposing joint surfaces, which was used as a surrogate for intra-articular stress. Findings: Distinct proximity patterns were observed across tasks with a recurrent pattern reported on the volar aspect of the first metacarpal. The comparison between healthy and arthritic subjects showed a significantly larger articular area, in parallel with a significant joint space narrowing and an increase in proximity area in arthritic subjects. We also observed severe articular deformations in subjects with late stage osteoarthritis. Interpretation: This study has increased our insight in the contact biomechanics of the trapeziometacarpal joint during tasks and positions of daily life in healthy and arthritic subjects, which might contribute to a better understanding of the occurrence mechanisms of degenerative diseases such as osteoarthritis. Highlights: An approach based on joint proximity is proposed to assess the contact biomechanics of the thumb. Proximity patterns of healthy and late stage osteoarthritic subjects were compared. Healthy group: distinct proximity patterns were observed between tasks. Osteoarthritic group: severe morphological changes were observed. Findings suggest an association between proximity patterns and osteoarthritis development.